2013
DOI: 10.1111/1742-6723.12136
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐related violence presenting to the emergency department: Is ‘glassing’ the big issue?

Abstract: Contrary to public perception generated by media, 'glassing' incidents, particularly at licensed venues, constitute a relatively small proportion of all alcohol-related violence. The current study highlights the predominance of young men injured following alcohol-related violence, demonstrating a key focus area within the population for aiming prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Previous research has identified home as a frequent place for alcohol‐related injuries to occur (Foster & Ferguson , Laing et al . ). The incidence of at‐home alcohol‐related injury presentations to EDs in previous studies ranges from 10% across a diverse range of 16 countries (Macdonald et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has identified home as a frequent place for alcohol‐related injuries to occur (Foster & Ferguson , Laing et al . ). The incidence of at‐home alcohol‐related injury presentations to EDs in previous studies ranges from 10% across a diverse range of 16 countries (Macdonald et al .…”
Section: Discussionmentioning
confidence: 97%
“…Alcohol-related violence and injury is a significant public health problem and a substantial burden on hospital EDs, especially on weekends during 'highalcohol hours' (HAH). 1,2 A recent Australasian snapshot of 106 EDs during HAH implicated alcohol in 14.3% of attendances, 3 with another Australian study showing the odds of major trauma being three times higher in patients with clinical evidence of intoxication. 4 These findings have been reflected internationally, with a large US hospital study demonstrating increasing scale of injury risk according to the number of alcohol drinks consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol‐related harm places substantial burden on hospital EDs, particularly on weekends during times of high alcohol use . This is of increased concern in Australia, with international research attributing a greater proportion of accident, injury and violence‐related attendances to alcohol use compared with US, European and South American hospitals .…”
mentioning
confidence: 99%